(3GdEJUGd GdNWGHj haf GdEbfGY (B/s - (3TYHGf, cQjeI GMSfs ((3GdCQOf(B-(3YeGf (B:s (3OGQ GSGeI ddfTQ h GdJhRjY ,s, 2015)
(3GdaUd GdGhd GYJHQg aUdG JegjOjG agh eQGLYI JGQjNjIQLYJ ef NdGdgG Gdi eGVj GdNWGHI aJYQVJ Gdi eaGgjegG h fTGJgG hQbjgG h YdGbJgG HGdYdhe GdGNQi ceG SdWJ GdVhA Ydi JWhQ GdNWGHI YfO Gge h GHQR GdYUhQ GdJj fTCJ h JWhQJ ajgG h g (B: (3GdYUQ GdjhfGfj GdLGgdj h GdESdGej(B. (3GeG GdaUd GdKGfj abO GfJbdJ ef NdGdg Gdi JGUjd eaghe GdGJUGd HGdYhOI Gdi GdNWGHI GdbOjeI QHW GdYdGbI Hjf eaghejf ef LejY GdRhGjG ceG hVMJ HTjA ef GdJaUjd eHGOF h GTcGd GdGJUGd GdJj JYJeO YdjgG GdNWGHI h ef Je HjfJ eG jSei HGdZJUGd GdNWGHj EfWdGbG ef GdEJUGd GdELJeGYj h GdaUd GdKGdK ef gPg GdOQGSI JfGhd GdEJUGd GdNWGHj h YdGbJg HGdEbfGYs
(3HjHdjhZQGajG(B:(3U(B.251-264s
Keywords: (3GdCOH GdYQHjs; (3af GdEbfGY s; (3GdEJUGd GdNWGHj s; (3GdNWGHI s